Protective Effects of Alpha-Lipoic Acid on Oleic Acid-Induced Acute Lung Injury in Rats - Bulmus, Funda Gulcu; Gursu, Mehmet Ferit; Muz, Mehmet Hamdi; Yaman, Ihsan; Bulmus, Ozgur; Sakin, Fatih (Galenos Publ House, 2013)
Background: Oxidative stress is believed to be an important factor in the pathogenesis of acute lung injury (ALI). Aims: The aim of this study was to investigate the possible protective role of alpha-lipoic acid (alpha-LA) on oleic acid (OA)-induced ALI in rats. Study Design: Animal experiment. Methods: A total of thirty-five rats were divided into five groups in the study. Group 1 served as a control group. Rats in Group 2 (alpha-LA) were administered alpha-LA intraperitoneally at a dose of 100 mg/kg body weight (SW). Rats in Group 3 (OA) were administered OA intravenously at a dose of 100 mg/kg BW. In Group 4 (pre-OA-alpha-LA), alpha-LA was given 15 minutes prior to OA infusion, and in Group 5 (post-OA-alpha-LA), alpha-LA was given two hours after OA infusion. Four hours after the OA infusion, rats were decapitated. Blood samples were collected to measure serum levels of malondialdehyde (MDA) and glutathione (GSH), and the levels of activity for superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px). Lung tissue samples were taken for histopathological examination. Results: Exposure to OA resulted in increases in serum MDA levels (p<0.001), as well as histopathological lesions in lung tissue, and decreases in CAT (p<0.05), GSH-Px (p<0.05) activities and GSH (p<0.05) levels. On the other hand, MDA levels were decreased significantly (p<0.001), while CAT (p<0.05), GSH-Px (p<0.01) activities and GSH (p<0.05) levels were increased significantly in the pre-OA-alpha-LA group compared with the OA group. Conclusion: alpha-LA was found to lessen oxidative stress and to have positive effects on antioxidants in cases of OA-induced ALI. In conclusion, alpha-LA appears to have protective effects against ALI and potential for the prevention of ALI.
Keywords: Acute lung injury; oleic acid; alpha-lipoic acid; oxidative stress